Keragaman Cendawan Kontaminan Pada Kacang Tanah (Arachis Hypogea L.) Di Pasar Tradisional Modern Kabupaten Maros - Pratiwi, Indah Astuti; Alhidayatullah, Alhidayatullah; Lasabuda, Taufan Eka Putra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
A study has been carried out with the title Diversity of Fungus Contaminants in Peanuts sold at Tradisional Modern Market, Maros Regency, Fungus is an organism that belongs to fungi and does not have chlorophyll so it is heterotrophic. Peanuts are one of the healthiest food ingredients that are widely consumed by humans. The purpose of this research was to find out whether the peanuts sold at the Tradisional Modern Market in Maros Regency were contaminated with fungi that were still within safe limits for consumption and to find out the type of fungus in the peanuts sold at the Tradisional Modern Market in Maros Regency. In this study, five samples were taken randomly from peanut traders in Tradisional Modern Market, Maros Regency. As for the results that have been obtained from observations in this study, namely in samples of peanuts contaminated by bacteria, Aspergillus sp. and Aspergillus niger Aspergillus sp. is a producer of mycotoxins which are harmful to human and animal health, the mycotoxins produced are aflatoxins which are carcinogenic toxins found in aflatoxins usually found in food products contaminated with Aspergillus flavus mold including nuts, corn, food and dried fruit and some other products meat, Based on the results of the study it can be concluded that the peanut samples sold at the Tradisional Modern Market in Maros Regency were contaminated with fungi and fungal bacteria in the peanut samples, namely Aspergillus sp. and Aspergillus niger as well as gram-positive bacteria.